INTERVENSI FISIOTERAPI UNTUK MENGATASI KELUHAN PADA KNEE OSTEOARTHRITIS DI RSUD IDAMAN BANJARBARU : STUDI KASUS - Rawina Rawina; Riza Rahmani; Arys Hasta Baruna (LPPM Universitas Abdurrab, 2023)
A 65-year-old man with complaints of pain in both knees since one year ago, especially when squatting, standing, going up and down stairs and walking long distances. The patient has a history of walking every day with a distance of 5 km. The VDS examination was silent, suppressed, and movement was found to be 1,3, and 5. On physical examination, there was tenderness, palpable warmth, crepitus, and limited ROM on knee extension movements. Functional examination of the Western Ontario and McMaster Universities arthritis index (WOMAC) obtained a moderate interpretation. Radiological examination found the conclusion of Osteoarthritis. The patient was diagnosed with osteoarthritis. The patient was then given therapy using Ultrasound 1Hz 0.2W/cm2, Trancutaneous Electrical Nerve Stimulation (TENS) 25mA, quadricep setting exercise, and passive stretching exercise where the therapy was given 3 times. At the end of therapy the patient will be re-evaluated with WOMAC where the results are results in an increase in function and a decrease in pain